Efecto del Bono de Desarrollo Humano en la desigualdad de ingresos en las provincias del Ecuador periodo 2007-2022 - Luna Jimenez, Dayanna Elizabeth (2024)
The Gini index in Ecuador has varied cyclically over time, reaching a value of 0.54 in 2007 according to INEC 2022. For this reason, this research has focused on examining the effect of the Bono de Desarrollo Humano (BDH) on income inequality in the provinces of Ecuador, through statistical and econometric techniques, in order to propose public policy strategies aimed at reducing income inequality in Ecuador. To achieve this objective, data were collected from the Encuesta Nacional de Empleo, Desempleo y Subempleo (ENEMDU) for the period 2007-2022, published by Instituto Nacional de Estadísticas y Censos (INEC), using the Generalized Least Squares (GLS) model and spatial models. The results obtained showed an inverted U-shaped trend in Ecuador between inequality and per capita income, while the BDH presents an increasing trend, with the exception of the Amazon region, which showed an inverted U-shaped trend. In addition, income inequality was found to negatively affect neighboring provinces. Therefore, policies should be directed to the State to review and update the BDH program to the neediest people and to monitor the correct use of the program by the beneficiaries, in order to avoid an increase in the levels of inequality in Ecuador.